EVALUATION OF RICE GENOTYPES FOR SEED VIGOUR AND ASSOCIATED TRAITS - P. SUJATHA; D. SANJEEVA RAO, P. MOUNIKA, K. JHANSI RANI, P. SENGUTTUVEL (The Journal of Research, PJTSAU, 2023)
The study was conducted to investigate the variation in seed vigour for seven rice genotypes. The experiment was conducted at Department of Seed Science and Technology, PJTSAU using Completely Randomized Design with three replications during the year 2020-2021. For all the genotypes, data pertaining to seed quality parameters were recorded. Highest seed germination (94 %), dry weight (11.77 mg), seedling vigour index II (1770) and field emergence (91 %) were recorded in Moroberekan. Highest seedling length (28.90 cm), seedling vigour index I (2553), electrical conductivity (14.94 μS/cm/g) were recorded in AUS 276. Highest speed of germination (13.04) and alpha amylase activity (428.50 mg/g) were recorded in IR 64. Lowest seed germination (84 %), seedling length (20.96 cm), seedling vigour index I (1770) and field emergence (83 %) were recorded in N-22. Lowest dry weight, seedling vigour index II, speed of germination, alpha amylase activity and electrical conductivity were recorded in RNR 15048 (4.60 mg, 391 mg), AUS (9.38, 255.95 mg/g) and Dular (6.78 μS/cm/g) respectively. The results indicate that among all the genotypes, Moroberekan recorded highest vigour, Vandana and IR 64 have medium vigour and N-22 and AUS 276 have lower vigour compared to other genotypes. High vigour contributes to their performance in early seedling vigour in field conditions especially in direct seeded conditions. Planting low vigour seeds causes reduced plant height, delayed panicle exsertion and anthesis, less tillering capacity and reduced yield which can be avoided by selecting genotypes with high seed vigour.